Metformin Mitigates Cartilage Degradation by Activating AMPK/SIRT1-Mediated Autophagy in a Mouse Osteoarthritis Model - Wang, Chenzhong; Yao, Zhenjun; Zhang, Yueqi; Yang, Yi; Liu, Jinyu; Shi, Yi; Zhang, Chi (Frontiers in Pharmacology, 2020)
Chondrocyte dysfunction is a key mechanism underlying osteoarthritis. Metformin has shown protective effects in many diseases. The present study aimed to investigate the effects of metformin on autophagy and apoptosis in the process of osteoarthritis. A mouse osteoarthritis model was set up by surgically destabilizing medial meniscus in the knee. Intra-articular injection of metformin or vehicle was applied in the right knee for eight weeks. Mouse articular chondrocytes were isolated and passaged for in vitro experiments. Small interfering RNA (siRNA) transfection was used to silence target genes. Western blotting, immunohistochemistry, transmission electron microscopy were used. After eight weeks, metformin restored surgery-induced upregulation of MMP13 and downregulation of type II collagen in the joint cartilage. In cultured primary murine chondrocytes, IL-1β aggravated apoptosis and catabolic response in a dose-dependent manner. In the presence of IL-1β, metformin increased phosphorylated levels of AMPKα and upregulated SIRT1 protein expression, leading to an increase in autophagy as well as a decrease in catabolism and apoptosis. Inactivating AMPKα or inhibiting SIRT1 prevented the augmented autophagy in the presence of metformin. Silencing AMPKα2, but not AMPKα1, reduced SIRT1 expression and downregulated autophagy in cultured chondrocytes. Metformin protects against IL-1β-induced extracellular matrix (ECM) degradation in cultured chondrocytes and in mouse osteoarthritis model through activating AMPKα/SIRT1 signaling. Metformin shed light on the treatment of osteoarthritis.